2016
DOI: 10.1371/journal.pone.0153831
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Changes in β0-Thalassemia/Hb E Disease

Abstract: The compound β°-thalassemia/Hb E hemoglobinopathy is characterized by an unusually large range of presentation from essentially asymptomatic to a severe transfusion dependent state. While a number of factors are known that moderate presentation, these factors do not account for the full spectrum of presentation. Mitochondria are subcellular organelles that are pivotal in a number of cellular processes including oxidative phosphorylation and apoptosis. A mitochondrial protein enriched proteome was determined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Reticulocytes of healthy individuals clear mitochondria by mitophagy during maturation, and terminally differentiated RBCs produce energy by glycolysis (29). However, it has been shown that mitophagy in β-thalassemia is impaired, resulting in retention of mitochondria in mature RBCs (30,31). Flow cytometry analysis of MitoTracker-labeled blood cells showed that essentially all reticulocytes from both WT and Hbb th3/+ mice contained mitochondria (MitoTracker + cells, Figure 9A).…”
Section: Resultsmentioning
confidence: 99%
“…Reticulocytes of healthy individuals clear mitochondria by mitophagy during maturation, and terminally differentiated RBCs produce energy by glycolysis (29). However, it has been shown that mitophagy in β-thalassemia is impaired, resulting in retention of mitochondria in mature RBCs (30,31). Flow cytometry analysis of MitoTracker-labeled blood cells showed that essentially all reticulocytes from both WT and Hbb th3/+ mice contained mitochondria (MitoTracker + cells, Figure 9A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Khungwanmaythawee et al. investigated the differential expression of mitochondrial proteins isolated from normal controls and β‐thalassemia/Hb E patients of different severities . Although 50 differentially regulated mitochondrial proteins were identified, none of them matched any protein identified by the earlier studies.…”
Section: Studiesmentioning
confidence: 91%
“…DNA purity was verified by determining the absorbance ratio of OD 260/280 and all samples were in the ratio range 1.8–2.0. Mitochondria were quantitated by qPCR essentially as described previously 47 , with each reaction containing 50 ng DNA template, 1X KAPA SYBR FastMaster Mix (Kapa biosystems, Inc., Wilmington, MA.) and 300 nM of the following specific primers: CYTB-mtDNA-f 5′AACTTCGGCTCACTCCTTGG3′, CYTB-mtDNA-r 5′CCAATGTATGGGATGGCGGA3′, FPN1A-nDNA-f 5′-CAAACCGCTTCCATAAGGCTTTGC3′, FPN1A-nDNA-r 5′-TTCTGCGGCTGCTATCGCTG-3′.…”
Section: Methodsmentioning
confidence: 99%